The emergence of dynamic residential property values owing to violent ethno-religious conflicts in Jos - Ahmad Aliyu, Aliyu; Kasim, Rozilah; Martin, David; Garkuwa, Abdu Ibrahim; Muhammad, Maryam Salihu (IISTE, 2016)
The previous models of landand landed property value indicators are of two types, viz: tangible andintangible location attributes. In the case of Jos, the intangible attribute oflocation is the prime mover of residential property value indicators in areasthat are prone to violence while tangible location attributes are the mainfactors that determining real estate value in violent free areas as indicatedin the findings of the study.Socio-economic background (level of education, income, occupation, gender,religion, household size, indiginity and the likes) of Jos residents played avital role in triggering the crisis which eventually influence the values ofresidential properties in the study area. A combination ofself-administered questionnaires and semi-structured interview were deemed mostsuitable as data collection tools for this research due to the advantagesobtained from both approaches.A total of 1000 questionnaires were administeredto the respondents. Out of 1000 questionnaires administered to the respondents,876 valid responses were used to analyse the information pertaining to theeffect of intangible location attributes on residential property value in Joscity. Stratified random sampling was also adopted in order to generate datafrom the professional estate surveyors and valuers. Out of 30 firms, 10 werechosen and 120 questionnaires were administered to them, that is, 12 for eachfirm. However, out of 120 questionnaires administered to the professionalfirms, only 110 were retrieved back. . Most of the data presented using simple percentage distribution tableswere also complimented with the aid of complete theoretical analysis for somedata that are not quantifiable in nature. The research found that highestdemand for residential property was found along the inner city of Jos by theMuslims because this is the area where Muslims are in the majority which withinthe central part of the study area. It was also discovered that the outskirt ofthe city witness high influx of Christians who have sold their houses in thepredominately Muslims areas. There is a proliferation of squatter settlements,suburbs, squalid areas, ghettos and slum areas in the outskirts of Jos. Thefindings of this research is, therefore, not in conformity with the findings ofsome researchers who challenges all the existing models of residential propertyvalue by looking at safety as another indicator of land and landed propertyvalue. This research however negates this assertion because safety or securityof life and property is not a different phenomenon inters of determining thevalues of residential property but rather is among the intangible location attributesas indicators of residential property value. There is a need on the part of theinvestors and property developers before embarking into building constructionto take into consideration intangible or invisible factors of location in orderto avoid wasting of capital in the study area. When carrying out feasibilityand viability appraisal, attention must be given to the issue of Intangiblelocation attributes